China's Trade Flows : Changing Price Sensitivies and the Reform Process - Dayal-Gulati, Anuradha (IMF Working Papers; Working Paper, 1999)
Over the past 20 years, the Chinese authorities have undertaken wide-ranging reforms of their exchange and trade systems that have steadily reduced the role of planning and increased the importance of market forces. As these reforms have taken root, relative prices and domestic and foreign demand would be expected to have played a bigger role in determining trade flows. Econometric estimates of export and import equations provide evidence that trade flows have indeed become increasingly price sensitive, owing to the gradual liberalization of the trade regime over time, and to the growing shares of foreign-funded enterprises and manufactures in total trade.